Oddziaływanie ideologii nazistowskiej na sądownictwo niemieckie w Generalnym Gubernatorstwie w latach 1939–1945 - Wrzyszcz, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
The intense criticism from the Nazi ideological perspective directed against the justice system particularly against the judiciary in Germany also caused certain consequences on the territory of the General Government. There was no introduction in GG, as opposed to the Reich, of judges’ or attorneys’ lists. However, it does not mean that there were no attempts to infl uence judges who ruled in the German judicial system. It seems that reasons which led to the gradual deterioration of the judiciary’s position in Germany also appeared in the General Government. Along the lines adopted in the Reich, there were some legislative changes made, the purpose of which was the “acceleration” and the “simplification” of the execution of justice. The administration of the justice department increased its supervision over courts and prosecutors by issuing a series of detailed instructions and directives. Under the auspices of the justice department of GG, constant ideological propaganda was spouted. It appears as though the role of the “reformer” was adopted by Otto Bauer, the chief of the Higher German Court in Krakow. He compiled a memorandum titled “Thoughts on the shape of the justice system in the General Government” and presented it to the chief of the Main Section of the Justice System in GG. Bauer’s views were promulgated among German judges.
Keywords: ideologia nazistowska; sądownictwo niemieckie; Generalne Gubernatorstwo